Artificial intelligence adoption in extended HR ecosystems: enablers and barriers. An abductive case research - Singh, Antarpreet; Pandey, Jatin (Frontiers in Psychology, 2024)
Artificial Intelligence (AI) has disrupted modern workplaces, like never before and has induced digital work-styles. These technological advancements are generating significant interest among HR leaders, to embrace AI in Human Resource Management (HRM). Researchers and practitioners, are keen to investigate the adoption of AI in HRM and the resultant human-machine collaboration. This research investigates HRM specific factors that enable and inhibit the adoption of AI in extended HR ecosystems and adopts a qualitative case research design with an abductive approach. It studies three well-known Indian companies (globally visible), at different stages of AI adoption in HR function. This research investigates key enablers like optimistic and collaborative employees, strong digital leadership, reliable HR data, specialized HR partners, and well-rounded AI Ethics. The study also examines barriers to adoption: inability to have a timely pulse check of employees’ emotions, ineffective collaboration of HR employees with digital experts as well as external HR partners, and not embracing AI Ethics. This research contributes to the theory by providing a model for AI adoption and proposes additions to Unified Theory of Acceptance and Use of Technology, in the context of AI adoption in HR ecosystems. The study also contributes to the best-in-class, industry HR practices and digital policy formulation, to reimagine workplaces, promote harmonious Human-AI collaboration, and make the work places future-ready, in the wake of massive digital disruptions.